Nutritional status of children with cancer and its effects on survival - Yarış, Nilgün; Akyüz, Canan; Coşkun, Turgay; Kutluk, Tezer; Büyükpamukçu, Münevver (The Turkish Journal of Pediatrics, 2002)
In the present study we aimed to determine the nutritional status of our patients and to assess its relationship with survival. The nutritional status of 47 patients with cancer was evaluated at diagnosis, three months after initiation of the treatment and at the end of therapy. Weight for height, height for age, and weight for age of children were expressed as percent of standard. Values for each nutritional index were converted into standard deviation (Z) scores. Three-year overall survival (OS) and event-free survival (EFS) rates of patients were determined according to their nutritional status. The overall prevalence of malnutrition at diagnosis was 29.8%. Three months later the malnutrition ratio reached 38.3% and then decreased again to 18.5% at the end of the therapy. Although the prevalence of malnutrition at the third month of treatment was significantly higher from the prevalence at diagnosis (p: 0.001) and at the end of the therapy (p: 0.009), the mean Z scores of the nutritional indexes before and during the treatment were not significantly different. The survival rates of malnourished patients were not different from those of well nourished patients. In conclusion, malnutrition is one of the main problems in children with cancer; however, nutritional status has no effect on survival.
Keywords: malnutrition; cancer; children; survival; prognosis